Challenges and stresses experienced by athletes and coaches leading up to the Paralympic Games - Dehghansai, N.; Pinder, R. A.; Baker, J.; Renshaw, I. (PLOS ONE, 2021)
The demands of high-performance sport are exacerbated during the lead up to the Major Games (i.e., Paralympics). The purpose of this study was to better understand the challenges experienced and strategies utilized by Australian athletes (n = 7) and coaches (n = 5) preparing for the Tokyo Paralympic Games using semi-structured interviews. The thematic analysis highlighted challenges specific to participants` sport (e.g., budgetary constraints, decentralized experiences, athletes with various impairments), personal life (e.g., moving cities to access coaching, postponing vocational/educational developments, isolation from social circles), and associated uncertainties (e.g., COVID-19, qualifications, accreditations). Participants managed these challenges by utilizing strategies to `anticipate and prepare` (e.g., detailed planning, effective communication, contingency plans) and `manage expectations` (e.g., understanding specific roles and boundaries, focusing on the process [i.e., effort over results]). Trust and communication between athletes and coaches was key in coaches` better understanding of how athletes` impairments interact with their training and competition environments and tailor support to each athlete`s unique needs. Last, participants reflected on the `pressure` of the Games due to their performance having an impact on their career trajectory `post-Tokyo` with some athletes contemplating retirement and others realizing the consequences of their performance on sport-related vocation and sponsorship. Coaches also accepted the success of their programs and job security will depend on outcomes at the Games. The findings from this study shed light on factors to consider to reduce challenges for teams preparing for major competitions but also highlight key practical implications to support athletes and coaches leading up, during, and post-major Games.